Valmiki: The Epitome of ‘Integral Life’ - Arnab Chakraborty (PostScriptum: An Interdisciplinary Journal of Literary Studies)
The paper, “Valmiki: The Epitome of ‘Integral Life,” focuses on the first play of Tagore as a literary masterpiece in exploring Aurobindonean concept of integral life. This study briefly discusses the meaning of integral life as propagated by Sri Aurobindo. Moreover, it seeks to explore the importance of transformation of consciousness in achieving integral life. Although, Valmiki Pratibha (or The Genius of Valmiki, 1881) is analysed from different angles by many critics over different time, very few critics have successfully addressed the play from the perspective of integral life. This paper also explores the practical implications of integral life as well as its success in shaping and rectifying one’s character even in today’s world.